2016
DOI: 10.1111/psyp.12633
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological responses to auditory change

Abstract: A comprehensive characterization of autonomic and somatic responding within the auditory domain is currently lacking. We studied whether simple types of auditory change that occur frequently during music listening could elicit measurable changes in heart rate, skin conductance, respiration rate, and facial motor activity. Participants heard a rhythmically isochronous sequence consisting of a repeated standard tone, followed by a repeated target tone that changed in pitch, timbre, duration, intensity, or tempo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 49 publications
8
30
1
Order By: Relevance
“…These hypotheses were largely confirmed, with many measures exhibiting strong main effects of arousal or valence and with few interactions, validating this set of psychophysiological tools for use in future investigations of music-evoked emotions. Moreover, the observed effects align closely with results obtained for emotional responses to nonmusical stimuli (Berntson et al, 1997;Berntson et al, 2007;Bouscein et al, 2012;Bradley & Lang, 2007;Chuen et al, 2016;Dawson et al, 2007;Gerger et al, 2014;Larsen et al, 2003;Tassinary et al, 2007). This finding suggests that these responses are common to both musical and everyday emotional experiences, thus contributing to the ongoing discussion about the nature of musical emotions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These hypotheses were largely confirmed, with many measures exhibiting strong main effects of arousal or valence and with few interactions, validating this set of psychophysiological tools for use in future investigations of music-evoked emotions. Moreover, the observed effects align closely with results obtained for emotional responses to nonmusical stimuli (Berntson et al, 1997;Berntson et al, 2007;Bouscein et al, 2012;Bradley & Lang, 2007;Chuen et al, 2016;Dawson et al, 2007;Gerger et al, 2014;Larsen et al, 2003;Tassinary et al, 2007). This finding suggests that these responses are common to both musical and everyday emotional experiences, thus contributing to the ongoing discussion about the nature of musical emotions.…”
Section: Discussionsupporting
confidence: 84%
“…Electrodermal measures are sensitive to a variety of musical characteristics, such as emotional expressiveness (Vieillard, Roy, & Peretz, 2011), tempo, genre (Dillman Carpentier & Potter, 2007), and unexpectedness (Egermann et al, 2013;Steinbeis, Koelsch, & Sloboda, 2006), but they have most commonly been shown to be associated with highly emotionally arousing musical stimuli (Gomez & Danuser, 2004;Khalfa et al, 2008;Lundqvist, Carlsson, & Hilmersson, 2009;Nater, Abbruzzese, Krebs, & Ehlert, 2006;Rickard, 2004). However, a number of studies have failed to find any influence of music on electrodermal activity (Blood & Zatorre 2001), have reported an inconsistent pattern of response between activity and emotional ratings (White & Rickard, 2015), or have attributed electrodermal activity to orienting responses from novelty or audible change in the stimuli rather than to emotional arousal from the music per se (Grewe et al, 2007;Chuen, Sears & McAdams, 2016). A similar picture exists concerning cardiovascular measures: some studies report effects of arousal increasing cardiovascular activity (Blood & Zatorre, 2001;Rickard, 2004;Salimpoor et al, 2009;Witvliet & Vrana, 2007), Psychophysiological Indices of Musical Emotions 8 whereas others report no effect (Guhn, Hamm, & Zentner, 2007;Lundqvist et al, 2009), or even cite decreased cardiovascular activity during reports of highly arousing emotions (White & Rickard, 2015).…”
Section: Measuring Music-evoked Emotions: Psychophysiological Approachesmentioning
confidence: 99%
“…The existing research indicated that sound had a significant effect on the function of the human nervous system [28][29][30][31]. The human nervous system is divided into the Central Nervous System (CNS) and the Peripheral Nervous System (PNS).…”
Section: Physiological Responsesmentioning
confidence: 99%
“…Responses of the sympathetic division of the ANS such as an increased (phasic) skin conductance response (SCR, i.e., sweat secretion), an increase of heart rate (HR), and respiration rate (RR) as well as responses of zygomaticus major (smiling) and the corrugator supercilii (frowning) muscles (electromyography [EMG] activity) typically reflect stress, attention 14,15 , or affective processing [16][17][18][19] . In terms of auditory responses, changes in SCR, HR, RR, and EMG activity -reflecting a startle [20][21][22] or orienting response 23 -have been associated with pitch changes 24,25 and tone loudness (the louder the sound, the greater the SCR amplitude 26,27 ) as well as deviations in timbre, rhythm, and tempo 27 . Additionally, physiological responses to music may indicate felt arousal and valence of acoustic features 19,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, physiological responses to music may indicate felt arousal and valence of acoustic features 19,28,29 . For example, faster and increasing tempi are associated with greater arousal [30][31][32][33][34] , increased SCR 27,31,35,36 and HR 31,35,37,38 , whereas slow-paced (low arousal) music reduces HR and breathing 39,40 . Loudness is positively correlated with arousal 32,41,42 , and, correspondingly, changes in SCR 43,44 and HR 32,45 .…”
Section: Introductionmentioning
confidence: 99%